Breeding depression of red flesh apple progeny containing both functional MdMYB10 and MYB110a_JP genes. Issue 2 (22nd March 2015) - Hamada, Yuka; Sato, Hideto; Otagaki, Shungo; Okada, Kazuma; Abe, Kazuyuki; Matsumoto, Shogo; Flachowsky, H.
Abstract In apple, two MYB transcription factors MdMYB10 (R6:MdMYB10) and MdMYB110a have been shown to be responsible for the type 1 and type 2 red flesh traits, respectively. While type 1 red‐fleshed apples are characterized by a red coloration not only in fruit flesh but also in vegetative tissues such as leaves and flowers, red pigmentation in type 2 red‐fleshed apples is limited at the fruit flesh. We have searched cultivars containing both functional MdMYB10 and MdMYB110a and then tried to breed new cultivars containing both functional genes by cross‐pollination of 'Geneva' (type 1) and 'Pink Pearl' (type 2). The cultivar having both genes should exhibit superior characteristics, such as a stable red flesh trait throughout fruit maturity, as type 1 reduces its colouring until maturity, whereas type 2 increases until maturity. We could not identify red‐fleshed cultivars having both genes; moreover, only one plant of 80 F1 progeny having both genes died in its juvenile stage. From the results, it was suggested that some sort of breeding depression must have occurred. We analysed the expression patterns of the genes within two F1 plants having either MdMYB10 or MdMYB110a gene and found that the expression pattern of MdMYB110a was different from that observed in 'JPP35' ('Jonathan' × 'Pink Pearl'). The MdMYB110a gene in the No. 2804 F1 plant derived from 'Pink Pearl' × 'Geneva' was expressed in the flesh from the beginning of the red coloration through maturity, and seemed to cause upregulation, not only the latter half, but also the first half of the gene in the anthocyanin pathway.